2023
DOI: 10.1038/s41467-023-36349-8
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal DNA-import apparatus is homologous to bacterial conjugation machinery

Abstract: Conjugation is a major mechanism of horizontal gene transfer promoting the spread of antibiotic resistance among human pathogens. It involves establishing a junction between a donor and a recipient cell via an extracellular appendage known as the mating pilus. In bacteria, the conjugation machinery is encoded by plasmids or transposons and typically mediates the transfer of cognate mobile genetic elements. Much less is known about conjugation in archaea. Here, we determine atomic structures by cryo-electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…S5C) ( 1 ). All solved structures of conjugation pili, both bacterial and archaeal, show a tight association of lipids with TraA subunits, with a 1:1 stoichiometric ratio for bacterial pili ( 2 5 , 15 ). It was suggested that one of the functions of this pilin:lipid association would be to facilitate reinsertion of the pilus subunits within the membrane during retraction events ( 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S5C) ( 1 ). All solved structures of conjugation pili, both bacterial and archaeal, show a tight association of lipids with TraA subunits, with a 1:1 stoichiometric ratio for bacterial pili ( 2 5 , 15 ). It was suggested that one of the functions of this pilin:lipid association would be to facilitate reinsertion of the pilus subunits within the membrane during retraction events ( 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…This study clearly shows that the pED208 pilus is involved in DNA transfer between donor and recipient cells separated by small or large distances. A physiological basis for conjugation at a distance may be supported by the mechanical robustness of the pili as it forms a resilient protective casing (or shaft) for DNA transfer between cells ( 3 , 24 ). This still leads to many unanswered questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is not possible to evaluate the contribution of PG phospholipids in vivo 36 , our sMD simulations clearly show their fundamental role in maintaining the integrity of the filament, including an effect on the Glu29-Lys41 salt bridge interaction, and how the filament more readily falls apart in the absence of the PG phospholipids under force, although secondary structure of individual pilin subunits is well-maintained regardless of the presence of absence of the PG phospholipids. Given the large sequence and structural conservation among F-pilin (TraA) encoded by IncF plasmids (Supplementary Figure 3 A and 3B ), their extensive interaction interface 10 , 11 , and the positive effect of phospholipid molecules on pilus structural stability, we postulate that other pili classes will also benefit from being structurally reinforced by the presence of phospholipids, as exemplified by the recent structures of minimised and archaeal conjugative pili 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…It is made of a major component, VirB2, and a minor one, VirB5. Pili may serve either as devices mediating attachment of the donor cell to the recipient cell, or as a conduit for relaxase/ssDNA transport, or both (Beltran et al, 2023; Goldlust et al, 2023). Some conjugative pili are capable of retraction, which will bring donor and recipient cells together.…”
Section: Introductionmentioning
confidence: 99%